Evaluation method for coal for ferro-coke.

The method evaluates the softening melting properties of coal with added N,N'-di-2-naphthyl-p-phenylenediamine to accurately assess ferrocoke strength and fusion rate, addressing the limitations of existing evaluation methods and ensuring high-quality ferrocoke production.

JP7647718B2Active Publication Date: 2025-03-18JFE STEEL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022160434
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-10-04
Publication Date
2025-03-18
Estimated Expiration
2042-10-04

AI Technical Summary

Technical Problem

Existing methods for evaluating coal for ferrocoke do not accurately assess the strength and fusion rate of ferrocoke, particularly for low MF coal and in the presence of high MF coal and varying iron ore ratios.

Method used

A method that evaluates the softening melting properties of coal by adding N,N'-di-2-naphthyl-p-phenylenediamine, a primary or secondary amine compound with an aromatic ring, as an index, to improve the accuracy of ferrocoke strength and fusion rate evaluation.

Benefits of technology

This method allows for accurate evaluation of ferrocoke strength and fusion rate, enabling the production of stable and high-quality ferrocoke, and preventing issues like poor discharge from the drying furnace due to fusion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647718000003
    Figure 0007647718000003
  • Figure 0007647718000004
    Figure 0007647718000004
  • Figure 0007647718000005
    Figure 0007647718000005
Patent Text Reader

Abstract

To propose a method for evaluating coal for ferro-coke capable of accurately evaluating strength of ferro-coke and a fusion rate in a carbonization furnace.SOLUTION: A method for evaluating coal as a raw material for ferro-coke produced by molding and carbonizing a mixture of coal and iron ore, comprises evaluating the softening and melting properties of coal, using physical property values regarding the softening and melting properties of the coal whose softening and melting properties have been improved by adding N,N'-di-2-naphthyl-p-phenylenediamine, which is a primary or secondary amine compound having an aromatic ring, as an index.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for evaluating coal, which is a raw material for ferro-coke obtained by carbonizing a mixture of coal and iron ore. [Background technology]

[0002] In order to operate blast furnaces efficiently, coke produced by carbonizing coal in a coke oven is charged into the furnace. The coke charged into the furnace serves the following roles: spacer to improve ventilation inside the furnace, reducing agent, heat source, etc. In recent years, a technology has been developed to use ferro-coke for metallurgy instead of coke in order to improve the reactivity of coke.

[0003] The manufacturing method of ferro-coke is assumed to be as follows: the main raw materials, coal and iron ore, are prepared in advance by crushing and drying, then stirred and mixed in a kneader with a few mass% of binder, and then molded in a double-roll molding machine, and these molded products are carbonized in a vertical carbonization furnace to produce ferro-coke. The carbonized ferro-coke is required to have a certain level of quality (strength, reactivity) as a blast furnace raw material, and it is also necessary for the molded products to be discharged from the carbonization furnace as individual particles without fusing together in the carbonization furnace, so the fusion rate of the molded products during carbonization is also important.

[0004] Thus, various qualities are required for ferro-coke, and the development of raw material evaluation technologies to control the quality is underway. For example, Patent Document 1 proposes a method for evaluating the influence on ferro-coke strength by the product of the CSN value of softening coal contained in the raw material and the blending ratio. Also, Patent Document 2 proposes using coal with a Gieseler maximum fluidity (MF) determined according to the proportion of crystallization water in iron ore. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2016 / 125727 [Patent Document 2] JP 2007-119602 A [Patent Document 3] International Publication No. 2016 / 136191 Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, raw material evaluation techniques for controlling the quality of ferro-coke have been studied but have not been fully established. For example, Patent Document 1 proposes a method for evaluating the influence on ferro-coke strength by the product of the button index value and the blending ratio of softening coal contained in the raw material. However, this method does not mention the influence of softening coal with CSN 2.0 or less. In addition, Patent Document 2 uses the maximum fluidity value measured by a Gieseler plastometer, but it is known that the measurement accuracy is not high for low MF coal (for example, MF 10 ddpm or less), which is expected to be used in large amounts in ferro-coke. Furthermore, Patent Document 1 and Patent Document 2 hardly consider methods for evaluating the influence on the briquette fusion rate during carbonization, and there is no fully established evaluation method, especially for softening coal with low MF.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to propose a method for evaluating coal for ferro-coke, which can accurately evaluate the strength of ferro-coke and the fusion rate in a carbonization furnace. [Means for solving the problem]

[0008] In order to achieve the above object, the inventors have produced ferro-coke by combining coal and ore of a plurality of brands and in a blending ratio, and have investigated the relationship between the properties and strength of the produced ferro-coke and the fusion rate of the briquettes during carbonization, thereby achieving the present invention.

[0009] That is, the present invention is a method for evaluating coal as a raw material for ferro-coke, which is obtained by molding and carbonizing a mixture of coal and iron ore, and is characterized in that the method for evaluating coal for ferro-coke evaluates the thermoplastic properties of the coal, the thermoplastic properties of which have been improved by the addition of N,N'-di-2-naphthyl-p-phenylenediamine, which is a primary or secondary amine compound having an aromatic ring, using as indicators physical property values ​​related to the thermoplastic properties of the coal.

[0010] In the method for evaluating coal for ferrocoke according to the present invention configured as described above, (1) The physical property value relating to the thermoplasticity and melting characteristics of the coal is the Gieseler maximum fluidity (MF); (2) The coal before the addition of the amine compound is a low-MF coal having a Gieseler maximum fluidity MF of 10 ddpm or less; (3) This evaluation method is used to evaluate the strength of ferro-coke and the adhesion rate of ferro-coke briquettes in a carbonization furnace. (4) This evaluation method is to be used when a high MF coal with a Gieseler maximum fluidity MF of 200 ddpm or more is combined with a low MF coal with a Gieseler maximum fluidity MF of 10 ddpm or less, and the weight ratio of the high MF coal to the total blend weight of the high MF coal and the low MF coal is 15 mass% or more; (5) This evaluation method shall be used when the weight ratio of iron ore to the total weight of coal and iron ore is 40 mass% or less. (6) producing ferro coke by carbonizing a coal blend containing coal evaluated as usable using the above-mentioned method for evaluating coal for ferro coke; This is believed to be a more preferable solution. Effect of the Invention

[0011] According to the present invention configured as described above, by evaluating the thermoplastic properties of coal using as indicators physical property values ​​related to the thermoplastic properties of coal whose thermoplastic properties have been improved by the addition of N,N'-di-2-naphthyl-p-phenylenediamine, which is a primary or secondary amine compound having an aromatic ring, it becomes possible to accurately evaluate the strength and the fusion rate in a carbonization furnace of ferro-coke obtained by molding and carbonizing a mixture of that coal and iron ore. This not only enables the stable production of high-quality ferro-coke, but also makes it possible to prevent unexpected problems such as poor discharge from the carbonization furnace due to fusion in the carbonization furnace. [Brief description of the drawings]

[0012] [Figure 1] 1 is a graph showing the influence of the MF value of high MF coal on the relationship between the log MF and ferro-coke strength DI of the coal to be evaluated to which an amine compound was added. [Diagram 2] 1 is a graph showing the effect of the MF value of high MF coal on the relationship between the log MF of the coal to be evaluated to which an amine compound has been added and the fusion rate of the briquettes during carbonization. [Diagram 3] 1 is a graph showing the effect of the blending ratio of high MF coal on the relationship between the log MF and ferro-coke strength DI of coal to be evaluated to which an amine compound was added. [Figure 4] 1 is a graph showing the effect of the blending ratio of high MF coal on the relationship between the log MF of the coal to be evaluated to which an amine compound has been added and the fusion rate of the briquettes during carbonization. [Diagram 5] 1 is a graph showing the effect of the blending ratio of iron ore on the relationship between the log MF of evaluation target coal to which an amine compound was added and the ferro-coke strength DI. [Figure 6] 1 is a graph showing the effect of the blending ratio of iron ore on the relationship between the log MF of coal to which an amine compound has been added and the fusion rate of the briquettes during carbonization. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the embodiments of the present invention will be described in detail. Note that the following embodiments are merely examples of devices and methods for embodying the technical ideas of the present invention, and are not intended to limit the configuration to those described below. In other words, the technical ideas of the present invention can be modified in various ways within the technical scope described in the claims.

[0014] The inventors produced ferro-coke by combining coal and ore of a number of brands and in a number of blending ratios, and investigated the relationship between the properties and strength of the coke and the fusion rate of the briquettes during carbonization, and found the following results.

[0015] When ferro-coke was produced using only low-softening coal (hereinafter referred to as low MF coal) with a Gieseler maximum fluidity MF of 10 ddpm or less, fusion hardly occurred, and no differences due to brand could be confirmed. On the other hand, when ferro-coke was produced by combining low MF coal with high-softening coal (hereinafter referred to as high MF coal) with a Gieseler maximum fluidity MF of 200 ddpm or more, it was found that the effect of each brand of low MF coal on the fusion rate differed even if there was no difference in the MF value of the low MF coal.

[0016] In order to evaluate this effect, various coal properties were investigated, and it was found that there is a correlation between the maximum fluidity (MF), a physical property value related to the thermoplasticity of coal to which N,N'-di-2-naphthyl-p-phenylenediamine has been added, as described in Patent Document 3, which is a method for evaluating the caking properties of non-caking coal used for coke, and the difference in the fusion rate of this low MF coal. This suggests that the caking properties of low MF coal affect the fusion of briquettes during carbonization, and it is presumed that this is because by adding a reagent such as N,N'-di-2-naphthyl-p-phenylenediamine that improves the thermoplasticity of coal to low MF coal, it is possible to evaluate slight differences in the caking properties of low MF coal that could not be detected by the conventional Gieseler plastometer method.

[0017] As described above, the evaluation method according to the present invention is effective for evaluating the fusion rate when high MF coal and low MF coal are combined. In particular, it is desirable to apply the evaluation method according to the present invention when the weight blending ratio of high MF coal when high MF coal and low MF coal are combined is 15 mass% or more with respect to the weight of the total coal. This is because, although there was no difference between brands because low MF coal particles have poor adhesion during carbonization and cannot fuse the briquettes together, when low MF coal and high MF coal are combined, the high MF coal can fuse the briquettes together by adhering to the high MF coal or low MF coal, and it is presumed that the slight difference in softening and melting properties between low MF coal brands affected the ease of adhesion at the interface between high MF coal and low MF coal.

[0018] In addition, since fusion does not occur when the blending ratio of iron ore, which is a non-meltable particle, is high, this evaluation method is effective when the weight ratio of iron ore is 40 mass% or less of the total weight of iron ore and coal combined. On the other hand, the impact on ferro-coke strength could be evaluated regardless of the ratio of high MF coal or iron ore. This is presumably because the adhesion between low MF coal particles, which does not affect the fusion of the briquettes, also affected the strength.

[0019] As for reagents that can be added to improve the thermoplasticity properties of coal, as in Patent Document 3, phenothiazine, carbazole, N-phenyl-1-naphthylamine, and the like that improve the thermoplasticity of coal other than N,N'-di-2-naphthyl-p-phenylenediamine can also be used for evaluation. EXAMPLES

[0020] The following provides a detailed description of the embodiments of the invention. In this example, the effect of blending low MF coal on the strength DI of ferro-coke and the fusion rate during carbonization was investigated by the following method. For the low MF coal, 0.5 g of N,N'-di-2-naphthyl-p-phenylenediamine, a primary or secondary amine compound having an aromatic ring, was added as a reagent to 5 g of coal with the same Gieseler maximum fluidity MF detected by the conventional Gieseler plastometer method, and four brands of coal, A to D, with different MFs (hereinafter, reagent-added MF) were selected. The conventional MF and reagent-added MF of coals A to D without the addition of the conventional reagent are shown in Table 1 below.

[0021] [Table 1]

[0022] One brand of low MF coal and one brand of high MF coal shown in Table 1 were crushed to 2 mm or less in total, and iron ore (pisolitic ore with T.Fe: 56 mass%) was crushed to 3 mm or less in total. In a high-speed mixer, asphalt pitch, coal tar, and soft pitch were added as binders to the crushed coal and iron ore at 2.4 mass%, 2.0 mass%, and 3.6 mass% of the total raw material weight, respectively, and kneaded while heating to 160 ° C. Then, in a molding machine with a roll size of 650 mmφ × 104 mm, the mixture was molded at a rotation speed of 2 rpm and a linear pressure of 1 to 4 ton / cm to obtain an egg-shaped molded product of 30 mm × 25 mm × 18 mm (6 cc). Next, the molded product was carbonized using the following laboratory-scale carbonization method (fixed bed). The molded material was filled into a carbonization can with a length of 200 mm, width of 60 mm, and height of 200 mm, and carbonized for 4 hours and 20 minutes by program heating at a maximum temperature of 850°C, and then cooled in a nitrogen atmosphere. After cooling, the ferro-coke was removed from the carbonization can, and the weight ratio of the sample in which two or more ferro-coke particles were fused was defined as the fusion rate, and the relationship between the fusion rate and the reagent-added MF of low-MF coal was investigated. It was confirmed that, in a pilot-scale continuous carbonization furnace with a capacity of 30 ton / day, the fusion rate was 30 mass% or less and the coal could be discharged without any trouble. The drum strength DI (150 / 15) of the obtained ferro-coke was measured, and the effect of the blending composition on the strength was investigated.

[0023] The relationship between the MF of high MF coal, blending ratio, low MF coal brand, and iron ore blending ratio, and the strength and fusion rate during carbonization of the obtained ferro-coke are shown in Table 2 below. The high MF coal blending ratio described here is the weight ratio of high MF coal to the total weight of coal, and the iron ore blending ratio is expressed as the weight ratio of iron ore to the total weight of coal and ore, both in mass%. As shown in Table 2, ferro-coke was prepared under various blending conditions, and its strength and fusion rate were measured.

[0024] [Table 2] *1: The blend ratio of high MF coal (mass%) is expressed as the weight ratio of high MF coal to the total amount of coal. *2: The iron ore blend ratio (mass%) is expressed as the weight ratio of iron ore to the total amount of coal and iron ore.

[0025] First, the blending ratio of high MF coal was fixed at 30 mass%, and the blending ratio of iron ore was fixed at 40 mass%, and the results of evaluating the effect of the MF of high MF coal are shown in Figures 1 and 2. The vertical axis of Figure 1 is the measurement result of the ferro-coke strength DI, and the vertical axis of Figure 2 is the measurement result of the coagulation rate during carbonization, and the horizontal axis is the reagent addition logMF of low MF coal in both cases. As shown in Figure 1, when the MF of high MF coal is in the range of 100 ddpm to 1000 ddpm, the drum strength DI (150 / 15) became higher as the reagent addition logMF of low MF coal increased. On the other hand, as shown in Figure 2, when the MF of high MF coal is 100 ddpm, the coagulation rate during carbonization was 0 mass%, regardless of the value of the reagent addition logMF of low MF coal, and when the MF of high MF coal is 200 ddpm or more, the coagulation rate during carbonization became higher as the reagent addition logMF of low MF coal increased. These results confirm that the evaluation of ferro-coke strength using the reagent-added MF of low MF coal is valid for all MF values ​​of high MF coal, and that the adhesion rate during carbonization can be evaluated when the MF of high MF coal is 200 ddpm or more.

[0026] Next, the effect of the blending ratio of high MF coal was evaluated using high MF coal with a MF of 200 ddpm, and the results are shown in Figures 3 and 4. The blending ratio of iron ore was fixed at 40 mass%. The vertical axis of Figure 3 is the measurement result of ferro-coke strength DI, and the vertical axis of Figure 4 is the measurement result of the cohesion rate during carbonization, and the horizontal axis is the reagent addition logMF of low MF coal in both cases. As shown in Figure 3, in the range of the blending ratio of high MF coal from 5 to 50 mass%, the drum strength DI (150 / 15) became higher as the reagent addition logMF of low MF coal increased. On the other hand, as shown in Figure 4, when the blending ratio of high MF coal was 5 mass%, the cohesion rate during carbonization was 0 mass% regardless of the value of the reagent addition logMF of low MF coal, and when the blending ratio of high MF coal was 15 mass% or more, the cohesion rate during carbonization became higher as the reagent addition logMF of low MF coal increased. From the above results, it was confirmed that the evaluation of ferro-coke strength using reagent-added MF of low MF coal is valid for all high MF coal blending ratios, and that the adhesion ratio during carbonization can be evaluated when the high MF coal blending ratio is 15 mass% or more.

[0027] Furthermore, the effect of the blending ratio of iron ore was evaluated by fixing the blending ratio of high MF coal to 30 mass% using high MF coal with MF of 200 ddpm, and the results are shown in Figures 5 and 6. The vertical axis of Figure 5 is the measurement result of the strength DI of ferro-coke, the vertical axis of Figure 6 is the measurement result of the adhesion ratio during carbonization, and the horizontal axis is the reagent-added MF of low MF coal. As shown in Figure 5, in the range of iron ore blending ratio of 10 to 50 mass%, the drum strength DI (150 / 15) became higher as the reagent-added log MF of low MF coal increased. On the other hand, as shown in Figure 6, when the blending ratio of iron ore was 50 mass%, the adhesion ratio during carbonization was 0 mass% regardless of the value of the reagent-added log MF of MF coal, and when the blending ratio of iron ore was 40 mass% or less, the adhesion ratio during carbonization became higher as the reagent-added log MF of low MF coal increased. From the above results, it was confirmed that the evaluation of ferro-coke strength using reagent-added MF of low MF coal is effective for all iron ore blending ratios, and the adhesion rate during carbonization can be evaluated when the iron ore blending ratio is 40 mass% or less.

[0028] From the above results, it was confirmed that when low MF coal of 10 ddpm or less is used as a ferro-coke raw material using the conventional Gieseler plastometer method, the effect on ferro-coke strength can be evaluated for any blending configuration by using reagent-added MF of low MF coal.Furthermore, when combining high MF coal and low MF coal, when the blending ratio of high MF coal is 15 mass% or more and the blending ratio of iron ore is 40 mass% or less, the reagent-added MF of low MF coal is effective in evaluating the fusion rate during carbonization. [Industrial Applicability]

[0029] The evaluation method for coal for ferro-coke according to the present invention makes it possible to accurately evaluate the strength and fusion rate in a carbonization furnace of ferro-coke obtained by molding and carbonizing a mixture of coal and iron ore evaluated according to the evaluation method of the present invention, and not only can it stably produce high-quality ferro-coke but it can also prevent unexpected problems such as poor discharge from the carbonization furnace due to fusion in the carbonization furnace, and is therefore industrially useful.

Claims

1. The present invention relates to a method for evaluating coal as a raw material for ferro-coke, which is obtained by molding and carbonizing a mixture of coal and iron ore, the method comprising the steps of: evaluating the thermoplastic properties of coal using, as an index, a Gieseler maximum fluidity (MF) relating to the thermoplastic properties of coal that has been improved by the addition of N,N'-di-2-naphthyl-p-phenylenediamine, which is a primary or secondary amine compound having an aromatic ring.

2. 2. The method for evaluating coal for ferro-coke according to claim 1, wherein the coal before the addition of the amine compound is a low-MF coal having a Gieseler maximum fluidity MF of 10 ddpm or less.

3. 3. The method for evaluating coal for ferro-coke according to claim 1 or 2, characterized in that the evaluation method is used for at least one of evaluating the strength of ferro-coke and evaluating the fusion rate of ferro-coke briquettes in a carbonization furnace.

4. 4. The method for evaluating coal for ferrocoke according to claim 3, characterized in that the evaluation method is used when a high MF coal having a Gieseler maximum fluidity MF of 200 ddpm or more is combined with a low MF coal having a Gieseler maximum fluidity MF of 10 ddpm or less, and the weight ratio of the high MF coal to the total blended weight of the high MF coal and the low MF coal is 15 mass% or more.

5. 5. The method for evaluating coal for ferro-coke according to claim 4, wherein the evaluation method is used when a weight ratio of iron ore to a total weight of raw materials including coal and iron ore is 40 mass% or less.

6. A method for producing ferro coke using the method for evaluating coal for ferro coke according to any one of claims 1 to 5, comprising carbonizing a coal blend containing coal evaluated as usable to produce ferro coke.

7. A method for producing ferro coke using the method for evaluating coal for ferro coke according to claim 3, comprising carbonizing a coal blend containing coal evaluated as usable to produce ferro coke.

Citation Information

Patent Citations

  • Method for producing ferrocoke

    JP2007119602A

  • Method for producing iron ore-containing coke

    JP2011032371A

  • Method for producing coke, coke, modified coal, modified blended coal, and method for modifying coal or blended coal

    JP2015040270A

  • Evaluation method of coal and manufacturing method of coke

    JP2017125206A

  • Selection method of modifying agent for improving flowability of coal, modifying agent, modifying method of coal, and production method of coke

    JP2022032852A